Analysis of Factors Affecting Regional Financial Independence in the Framework of a Policy Strategy For Increasing Regional Original Income - Vissia Dewi Haptari; Ari Mulianta Ginting; Ferdinand David Aritonang (Green Publisher Indonesia, 2022)
The regional autonomy policy, which is accompanied by the provision of balancing funds, has a goal, one of which is to have an impact on the financial independence of regency/municipal governments in Indonesia. The balancing funds provided should have an effect or have an impact on regional financial independence. This research is directed to see to what extent the relationship of fiscal decentralization can provide an increase in regional financial independence. Based on the results of the panel data regression analysis of the district/city data clusters, the results showed various results. In clusters I and IV, it shows that there is a positive and significant effect of the provision of balancing funds on regional financial independence. Meanwhile, based on the results of panel regression analysis in regencies/cities in cluster II, it shows that the provision of balancing funds has no significant effect on regional financial independence. The districts/cities in cluster III show that the balancing fund variable has a negative and significant influence on the financial independence of local governments. This implies that the provision of balancing funds for districts/cities in cluster III actually makes local governments dependent on transfer funds from the central government.